Sustaining Low-Native-Fit Sponsorship Through Analogical Articulation with Functional Attributes - Wen-hao Winston Chou; Jeong-yeob Han; Yiran Su; James J. Zhang; Yi Zhang (SAGE Open)
Brands can deploy analogical reasoning as a means to articulate an incongruent sponsorship and improve fit perception between a property and its sponsor. Nevertheless, challenges remain for sport marketers regarding how best to leverage analogical articulation in sponsorship-linked advertising (SLA) to achieve the best outcomes. The current research expands on previous work by testing the effects of different types of analogical articulation (presence vs. absence of functional attributes) on consumers’ recognition of, attitudes concerning, and purchase intention toward a sponsor that does not naturally align with the property at hand. The results indicate that SLA that uses functional attributes in analogical articulation leads to greater degrees of favorable consumer attitudes toward the sponsor. Accordingly, sponsors lacking native fit should focus on their product or service’s functional attributes and actively explore creative ways to connect them to the sponsorship through analogical articulation in SLA.